Intratumor Heterogeneity and Its Impact on Drug Distribution and Sensitivity. Issue 2 (14th May 2014) - Fuso Nerini, I; Morosi, L; Zucchetti, M; Ballerini, A; Giavazzi, R; D'Incalci, M
<x xml:space="preserve">Abstract</x> We provide an overview of the available information on the distribution of chemotherapeutics in human tumors, highlighting the progress made to assess the heterogeneity of drug concentrations in relation to the complex neoplastic tissue using novel analytical methods, e.g., mass spectrometry imaging. The increase in interstitial fluid pressure due to abnormal vascularization and stiffness of tumor stroma explains the variable and heterogeneous drug concentrations. Therapeutic strategies to enhance tumor drug distribution, thus possibly increasing efficacy, are discussed. Clinical Pharmacology & Therapeutics (2014); 96 2, 224–238. doi:10.1038/clpt.2014.105